Restoring Connections and Cultivating an Ecological Self through Ecotherapy in Ibsen`s The Lady From the Sea - Banu Akçeşme; Çağrı Şarlar (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
This article aims to provide ecopsychological insight into the characters in Ibsen`s play The Lady From the Sea. There are two types of characters in the play who can be categorized as society-oriented and nature-oriented. While the society-oriented characters are ecologically ignorant and oblivious to the detrimental effects of their disconnection from nature, the nature-oriented characters actively seek ways to address their frustration and dissatisfaction stemming from the broken ties between socio-cultural, psychological, and natural realms and they aim to improve their dysfunctional relationships with the self, community, and natural environment through ecotherapy. Ecotherapy is a term defined in terms of outdoor activities such as greencare, green exercise, and physical embeddedness and immersion that provide therapeutic treatment by fostering an appreciation for nature and acknowledging its intrinsic value. Thus, this play offers a story of healing and the restoration of emotional, mental, and natural landscapes, highlighting their inseparable interrelation. This article intends to argue that positive emotions that arise from engagement with nature augment physical, mental, psychological and behavioral processes and the characters who establish meaningful interaction with nature can deal more effectively with stressful, undesirable or unpleasant experiences and situations.